Study of pregnancy outcome in women with cardiac disease: a retrospective analysis - Pandey, Kiran; Verma, Kavita; Gupta, Shruti; Jahan, Uruj; Kirti, Neha; Gupta, Pundrik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cardiac disease complicates 1% of all pregnancies. It is one of the 3 major indirect causes of maternal mortality in India. Objective of the study is to evaluate the maternal and fetal outcome in patients with cardiac disease in pregnancy. Methods: A retrospective analysis was carried out in 117 pregnant women with known or newly diagnosed heart disease from January 2013 to December 2015 at a tertiary care hospital. Results: In the present study, the incidence of cardiac disease was 0.8%. Majority 66 (56.4%) were of 23-27 years of age, 72 (61.5%) were primigravida. Mostly 84 (71.8%) belonging to New York Heart Association (NYHA) Class I and II. Rheumatic heart disease seen in 96 (82.1%) and congenital heart disease in 17.9% subjects. Among RHD Mitral stenosis was the most common, seen in 51 (53.1%) cases. Majority 78 (66.6%) had vaginal delivery and caesarean section in 28 (23.9%) cases. Most common maternal complication was anaemia seen in 54 (46.2%) cases, congestive cardiac failure complicated 23 (19.6%) cases. 18 patients required ICU care and maternal mortality in 6 cases (5.12%). The live births in (94.8%) cases, 33 (28.2%) babies required NICU admission and perinatal mortality was 7.7%. Conclusions: Heart disease in pregnancy is a high risk condition and has a major impact on pregnancy outcome. Rheumatic heart disease being the prominent cardiac lesion. Fetomaternal mortality and morbidity can be reduced with proper antenatal, intrapartum and postnatal care in conjunction with cardiologist and neonatologist.